Gender disparities in health and healthcare: results from the Portuguese National Health Interview Survey Disparidades de gênero na saúde e nos cuidados de saúde: resultados para Portugal com base no Inquérito Nacional de Saúde - Julian Perelman; Ana Fernandes; Céu Mateus (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Although women experience poorer health conditions during their lives, they live longer than men. The main explanations for this paradox suggest that women's excess of ill-health is limited to minor illnesses and their different attitudes toward health. The authors test these assumptions by investigating disparities between men and women in health and healthcare in Portugal. Data are used from the Portuguese National Health Interview Survey 2005/2006 (N = 33,662). Multivariate regressions showed that women were more likely to report worse self-rated health, more days with disability, higher prevalence of hypertension, chronic pain, cancer, anxiety and depression, and more medical consultations. Heart disease was significantly more prevalent among men, possibly explaining part of the paradox. Women's more frequent use of medical consultations may reflect their heightened awareness of health problems, which may protect them against early death. Gender differences in socioeconomic status explain part of the differences in health, but fail to provide a complete understanding. Embora tenham pior saúde ao longo da vida, as mulheres vivem mais anos do que os homens. As principais explicações para este paradoxo são que as mulheres sofrem mais de doenças menores, e adotam atitudes diferentes em relação à saúde. Testamos essas hipóteses pela investigação de disparidades entre homens e mulheres na saúde e nos cuidados de saúde em Portugal. Os dados usados são do Inquérito Nacional de Saúde 2005/2006 (N = 33.662). Regressões multivariadas mostram que as mulheres declaram pior estado de saúde autoavaliado, maior número de dias de incapacidade, maior prevalência de hipertensão, dor crônica, cancro, ansiedade e depressão, e maior utilização de consultas. A doença cardíaca é significativamente mais prevalente nos homens, o que pode explicar em parte o paradoxo. A maior utilização de consultas nas mulheres pode refletir a sua maior consciência relacionada com a saúde, que talvez seja protetora contra a morte precoce. Diferenças de gênero no estatuto socioeconômico explicam parte das diferenças em saúde, mas não permitem uma compreensão completa das diferenças.